Amiodarone-Induced Thyrotoxic Thyroiditis: A Diagnostic and Therapeutic Challenge. (12th November 2014) - Barvalia, Umang; Amlani, Barkha; Pathak, Ram
Abstract : Amiodarone is an iodine-based, potent antiarrhythmic drug bearing a structural resemblance to thyroxine (T4). It is known to produce thyroid abnormalities ranging from abnormal thyroid function testing to overt hypothyroidism or hyperthyroidism. These adverse effects may occur in patients with or without preexisting thyroid disease. Amiodarone-induced thyrotoxicosis (AIT) is a clinically recognized condition commonly due to iodine-induced excessive synthesis of thyroid, also known as type 1 AIT. In rare instances, AIT is caused by amiodarone-induced inflammation of thyroid tissue, resulting in release of preformed thyroid hormones and a hyperthyroid state, known as type 2 AIT. Distinguishing between the two states is important, as both conditions have different treatment implications; however, a mixed presentation is not uncommon, posing diagnostic and treatment challenges. We describe a case of a patient with amiodarone-induced type 2 hyperthyroidism and review the current literature on the best practices for diagnostic and treatment approaches.